2017
DOI: 10.13189/ujam.2017.050201
|View full text |Cite
|
Sign up to set email alerts
|

A New Analytical Method for Solving General Riccati Equation

Abstract: In this paper, the general Riccati equation is analytically solved by a new transformation. By the method developed, looking at the transformed equation, whether or not an explicit solution can be obtained is readily determined. Since the present method doesn't require a proper solution for the general solution, it is especially suitable for equations whose proper solutions cannot be seen at a first glance. Since the transformed second order linear equation obtained by the present transformation has the simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…More interestingly, the Riccati equation can be transformed into second order OLDE by using the transformation = − ′ ( ) as discussed by Busawon and Johnson (2005). The study made by Busawon and Johnson (2005) and Pala and Ertas (2017) showed that Eq. 1 and 2 are inter-convertible.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…More interestingly, the Riccati equation can be transformed into second order OLDE by using the transformation = − ′ ( ) as discussed by Busawon and Johnson (2005). The study made by Busawon and Johnson (2005) and Pala and Ertas (2017) showed that Eq. 1 and 2 are inter-convertible.…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts have also been made to solve Riccati Eq. 2 in the form of special cases in the literature Al Bastami et al (2010), Batiha (2015), Busawon and Johnson (2005), Pala and Ertas (2017), and Sarafian (2011) but once again there is no general method to solve (2) in its general form Al Bastami et al (2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As soon as differential equations were invented, the Riccati differential equation was the first one to be investigated extensively since the end of the 17th century [22]. This equation appears widely in large variety of applications in engineering and applied science such as random processes, diffusion problems, optimal control etc., [1,11,12,15]. It has the form where a(x), b(x) and c(x) are continuous functions of x.…”
Section: Introductionmentioning
confidence: 99%